2022
DOI: 10.7759/cureus.28152
|View full text |Cite
|
Sign up to set email alerts
|

Osteitis Condensans Ilii: A Case Series

Abstract: Osteitis condensans ilii (OCI) is a rare self-limiting low back pain syndrome. It is an incidental imaging discovery around sacroiliac joints with distinctive sclerotic lesions. We present three case reports as a series. In the first case, a 38-year-old female presented with unresolved chronic low back pain for eight years. She had bilateral triangular sclerosis of the ilium abutting sacroiliac joints and other causes of back pain were ruled out. Non-operative management was successful. In the second case, a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Various authors have reported a single case or case series of OCI [3,6]. This case is atypical in the sense that it started one year after the last delivery of the patient.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various authors have reported a single case or case series of OCI [3,6]. This case is atypical in the sense that it started one year after the last delivery of the patient.…”
Section: Discussionmentioning
confidence: 98%
“…Hip flexion, abduction, and external rotation result in unpleasant and vague distress. Other provocative tests, including iliac compression, sacral distraction, and thigh/sacral thrust tests, are usually negative [6].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment is the mainstay and primary modality in the management of OCI. [21] The pain medication, physiotherapy, and steroid injection are advised on case by case basis. [22] Mostly, the symptoms are self-limiting, and the resolution of radiological sclerosis is also described with time.…”
Section: Treatmentmentioning
confidence: 99%
“…leaf on a ZnO solid and used it for hydrogen generation through ethanol photoreforming, its catalytic performance being higher than that achieved on reference material P25 TiO2 [5]. Sathu et al [6] used champa (Plumeria Magnolia champaca) tree leaves as templates for ZnO and tested it for benzene to phenol oxidation under UV light. Hashemizadeh et al [7] replicated Camellia leaves morphology on artificial titania leaves.…”
Section: Introductionmentioning
confidence: 99%